Investigating Self-Awareness and Speaking Ability Correlations in Secondary EFL Education - Nurmiati, Nurmiati; Putri, Andi Mega Januarti; Junaedi, Ahmad (Universitas Sulawesi Barat, 2024)
This study investigates the correlation between self-awareness and English-speaking ability among second-grade students at SMAN 3 Majene, Indonesia. Employing a quantitative correlational design, the research examined 17 students selected through cluster random sampling from a population of 51. Data were collected using a self-awareness questionnaire assessing emotional awareness, self-assessment, and self-confidence, alongside a speaking ability test. Results revealed high levels of self-awareness among participants, with most reaching the